2007
DOI: 10.1104/pp.107.105940
|View full text |Cite
|
Sign up to set email alerts
|

Functional Sieve Element Protoplasts

Abstract: Sieve element (SE) protoplasts were liberated by exposing excised phloem strands of Vicia faba to cell wall-degrading enzyme mixtures. Two types of SE protoplasts were found: simple protoplasts with forisome inclusions and composite twin protoplasts-two protoplasts intermitted by a sieve plate-of which one protoplast often includes a forisome. Forisomes are giant protein inclusions of SEs in Fabaceae. Membrane integrity of SE protoplasts was tested by application of CFDA, which was sequestered in the form of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 33 publications
2
40
0
1
Order By: Relevance
“…Induction of sieve-plate occlusion by electropotential waves (Fromm and Bauer, 1994;Furch et al, 2007) and turgor shocks (Knoblauch et al, 2001;Hafke et al, 2007) triggers a release of Ca 2+ into the SE lumen which then induces occlusion. Furch and colleagues demonstrated that sieve-tube occlusion is reversible probably through active removal of Ca 2+ ions.…”
Section: Discussionmentioning
confidence: 99%
“…Induction of sieve-plate occlusion by electropotential waves (Fromm and Bauer, 1994;Furch et al, 2007) and turgor shocks (Knoblauch et al, 2001;Hafke et al, 2007) triggers a release of Ca 2+ into the SE lumen which then induces occlusion. Furch and colleagues demonstrated that sieve-tube occlusion is reversible probably through active removal of Ca 2+ ions.…”
Section: Discussionmentioning
confidence: 99%
“…The third explanation is based on the knowledge that the formation of mature phloem sieve elements and companion cells from meristematic tissue involves a controlled process of programmed cell death, resulting in anucleate sieve elements, which are linked to companion cells by complex plasmodesmatal connections. Despite a recent report (Hafke et al, 2007), the production of transcriptionally functional protoplasts from anucleate tubes is self-inconsistent, and would be problematic for companion cells. Furthermore, the process of protoplast sorting discriminates in favor of protoplasts that are mechanically resilient, whereas that of nuclear sorting automatically excludes anucleate cells or cells in mitosis.…”
Section: Comparison To Protoplast Sortingmentioning
confidence: 99%
“…Callose deposition was restricted to a distance of about 0.5 cm from the site of cutting and results from local wound effects. In the vicinity of cutting loss of turgor pressure may cause activation of mechano-sensitive Ca 2+ -channels 21 , but reduced Ca 2+ -influx into the SE lumen is not sufficient to induce callose production further away from the cut. In conclusion, forisome dispersion may have a lower Ca 2+ threshold than callose synthesis.…”
Section: Wounding Reactions and Passage Of Epws After Cutting The Maimentioning
confidence: 99%